1992
DOI: 10.1007/bf00054189
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lobenzarit on murine acute viral myocarditis

Abstract: Lobenzarit (CCA) is a newly developed immunomodulating drug that has been demonstrated to enhance suppressor T-cell number and function. In this study we investigated the effect of CCA on murine myocarditis induced by the encephalomyocarditis (EMC) virus. Mice were first inoculated with the EMC virus. CCA (100 mg/kg) was administered daily for 14 days, starting on the day the mice were inoculated. The concentrations of Lyt2+ (suppressor/cytotoxic T) cells in the peripheral blood and heart were examined by lase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…A recent study reported that CCA blocked HLA-DR antigen expression on endothelial cells [23]. To our knowledge, however, there is only one reported study of the effects of CCA upon acute myocarditis [13], where immune or autoimmune mechanisms are thought to be involved in the pathogenesis [1,2].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A recent study reported that CCA blocked HLA-DR antigen expression on endothelial cells [23]. To our knowledge, however, there is only one reported study of the effects of CCA upon acute myocarditis [13], where immune or autoimmune mechanisms are thought to be involved in the pathogenesis [1,2].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of T-cell activation disclosed that the signal transduction pathway is set in motion by multiple activating signals. As for the field of myocarditis, Yokoyama et al reported that CCA increased the peripheral Ly2 population (CDS) in encephalomyocarditis virus murine acute myocarditis, and enhanced myocardial damage [13]. The difference between these two viruses regarding the number of T-cell subsets in virus-infected drug-treated mice is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[55] In a similar model, lobenzarit, a disodium immunomodulatory drug known to enhance suppressor T cell activity, was shown to increase both T cell response to, and the severity of myocarditis induced by, ECMV. [56] However, when used to treat mice infected with Coxsackie virus B3, lobenzarit mitigated the immune response to viral infection. [57] Despite encouraging data with these agents specific to lymphocyte immunosuppression, attempts to use more general immunosuppressant agents, such as cyclosporine and prednisolone, have been shown to enhance mortality in mice infected with ECMV.…”
Section: Immunosuppressive Therapiesmentioning
confidence: 99%